Model Pembelajaran Cooperative Integrated Reading And Composition (CIRC) Dalam Pembelajaran Pendidikan Agama Islam (Tazakka: Jurnal Pendidikan dan Keislaman, 2023)
Students have difficulty improving in thematic learning, so we need interesting media for students by using flashcards (picture cards) in learning. The purpose of this study was to determine the effect of flashcard learning media (picture cards) on improving learning outcomes for elementary school students. This type of quasi-experimental research. The population in this study were all students in grades VA and VB as many as 36 students. Sampling was carried out using the Saturated Sampling technique and the class selected as the experimental class was VA and the control class was VB. Data collection techniques were carried out by observation, testing and documentation. The data analysis technique was carried out by normality test, homogeneity test, and hypothesis testing using SPSS 26. The research results based on data analysis, obtained that the rcount hypothesis test value is greater than rtable with a significant level of 5% for N 18 rtable is 0.468%, then the hypothesis Ha: there is an effect of the use of flashcard learning media (picture cards) on improving learning outcomes for fifth grade elementary school students by 33.55%.
Keywords: Media Flashcard (picture card); Learning Outcomes; Elementary School